ABCA3 Deficiency: an unusual cause of respiratory distress in the newborn - Anandarajan, Mugilan (The Ulster Medical Society, 2009)
Respiratory Distress Syndrome (RDS) is due to deficiency of surfactant and commonly occurs in preterm babies. We report the first confirmed case in Northern Ireland of ABCA3 transporter deficiency which is a rare but important cause of RDS in term babies. A 38 week gestation female infant developed respiratory distress at four hours of age. Chest radiography was consistent with RDS. The baby required repeated doses of surfactant, each resulting in transient periods of decreased ventilatory requirement and improvement in blood gases, but unfortunately she did not survive. DNA sequencing demonstrated two different mutations in the ABCA3 gene, one inherited from each parent. The baby was therefore a compound heterozygote, and both mutations were thought to be functionally significant. ABCA3 transporter deficiency is a genetic disorder that is increasingly recognized as a cause of RDS in term babies in whom congenital deficiency of surfactant B and abnormalities of surfactant protein C have been excluded. It should be considered in mature babies who develop severe RDS.